Faith Alone is Essential for Salvation - Johnson Jr, Anthony J (International Journal of Scientific Research and Management (IJSRM), 2025)
This thesis argues that faith alone (sola fide)—rather than the act of baptism—is the true cornerstone of salvation, a distinction underscored by the deliberate omission of baptism in key biblical passages emphasizing justification. Mark 16:16 states, “He that believeth and is baptized shall be saved; but he that believeth not shall be damned,” highlighting that condemnation is linked to unbelief, not the absence of baptism. This study contends that salvation is a gift of grace received through faith alone, supported by biblical doctrine, historical context, and theological debate.Through biblical analysis, this paper defends sola fide by examining Ephesians 2:8-9, Romans 3:28, and Galatians 2:16, which affirm that salvation is granted by faith in Christ, independent of works or adherence to religious rites. These passages reinforce that righteousness before God is imputed through faith alone rather than achieved through human effort or sacramental participation.From a historical perspective, this study demonstrates that sola fide has deep roots in early Christian teachings, was solidified during the Reformation, and continues to shape Protestant theology. The research highlights how Martin Luther, John Calvin, and other Reformers rejected sacramental justification, emphasizing that faith alone is the means of salvation. Despite theological disputes, this doctrine has remained central to Protestant identity.From a theological standpoint, the debate over sola fide continues to be a major point of contention between Christian traditions. Protestant Reformers defended justification by faith alone against Catholic and Orthodox teachings that emphasize a synergy between faith, works, and sacraments. These doctrinal differences have led to enduring theological discussions on the relationship between faith, baptism, and salvation.Furthermore, this research discusses the dilemma of ongoing theological debates over sola fide, considering the consequences of differing interpretations and the obstacles they present to Christian unity. It addresses legalism and self-righteousness, contrasting these with the biblical understanding of grace while also cautioning against antinomianism, which distorts sola fide as an excuse for moral laxity. The study also examines the modern ecumenical movement, exploring efforts to reconcile Protestant, Catholic, and Orthodox views on justification and the role of baptism in salvation.